The Effect of Perceived Risk on Intention to Quit Smoking - Ririn Wulandari; Mahrinasari MS (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study analyzes the factors that influence the attitude toward not smoking and its effect on the intention to quit smoking with utilitarian, hedonic, and risky behavior considered as a moderating variable.Methodology: This quantitative analysis research uses the Structural Equation Modeling (SEM) method with the Smart-PLS program. The research population was smokers who live in Jakarta, Lampung, and other areas in Indonesia. The population size is not known with certainty, therefore the determination number of samples uses The Hair Method to determine the number of samples which is 5 x the number of indicators. The number of indicators is 20 so the minimum sample is 100. The number of respondents who met the requirements was 117 out of 232. The sampling technique used was nonprobability sampling with judgment.Finding: The results of this study indicate that only the perception of risk affects the intention to quit smoking and the attitudes that are built from awareness do not make intentions appear.Conclusion: Based on the results of this study, it is necessary to add information and develop a marketing strategy for a smoking cessation campaign regarding future health risks and risks to others, especially loved ones